Connecting Nuclear Security to International Frameworks on Gender and Security - Kathleen A Doty; Jessica S Burniske (International Journal of Nuclear Security, 2023)
The international community is slowly beginning to recognize the intersections between law and policy as it relates to international security—particularly arms control, nonproliferation, and disarmament—and the body of human rights law that addresses gender equality. Notably absent from this discussion is the field of nuclear security. Despite its historical underpinnings as an inherently domestic activity, nuclear security is thoroughly grounded in international treaty law. However, nuclear security is often overlooked in the international security context and has not been well-situated in international instruments that address gender equality. We argue that gender equality in nuclear security should be understood as an important component of broader efforts to achieve equal opportunities for women in work and is critical to ensuring women are included in conflict prevention efforts. Linking nuclear security to broader international efforts to increase gender equality in security and conflict prevention will provide a clearer structure and framework for gender equality initiatives in the nuclear security field. This link is critically important given that estimates indicate that women comprise only 20% of the nuclear workforce. Moreover, situating nuclear security in a broader international legal framework will simultaneously help states meet their gender equality commitments emanating from other instruments. This paper will first analyze the relationship between nuclear security and broader international security efforts, in particular arms control treaties and nonproliferation regimes. It will then survey the relevant international and regional frameworks for gender equality, particularly those that have applicability in the security context. This paper will next explore the relationship between nuclear security and these frameworks on gender. We find that some instruments provide support for gender equality initiatives in nuclear security because of their mandate to states to provide structural gender equality, and others are particularly relevant when they call for women’s participation in conflict prevention. This paper concludes with recommendations to states that are concerned about the underrepresentation of women in nuclear security.
Keywords: Nuclear security; non-proliferation; conflict prevention; gender; gender equality; security